A study of efficacy and feasibility of laparoscopic surgery in a tertiary care center, Pokhara, Nepal - Shrestha, Anuj; Bijukchhe, Sunil Man; Bhattarai, Anand; Neupane, Bhojraj; Kaushal, Ketki (Journal of Gandaki Medical College-Nepal, 2021)
Introduction: Laparoscopic surgery is the gold standard technique for most of the gastrointestinal surgeries in developed countries. However, challenges in developing countries, apart from cost of instrumentation, include lack of awareness. Therefore, the aim of this study is to determine the efficacy and feasibility of laparoscopic surgeries in our part of the world.Methods: Retrospective, cross-sectional study was carried out from January 1, 2018 to June 30, 2019. Patient’s information on demographic details, type of laparoscopic surgery, operation time, length of hospital stay, reasons for conversion to open surgery, and intra-operative and post-operative complication details were retrieved from the operation log book and patient’s chart.Results: A total of 380 patients that underwent laparoscopic surgeries were included in the study. Out of 193 patients that underwent laparoscopic cholecystectomy, there were 144 (74.61%) females and 49 (25.38%) males with conversion rate of 4.66% and post-operative complication rate of 8.80%. Similarly, among 136 patients that underwent laparoscopic appendectomy, there were 68 (50%) females and 68 (50%) males with conversion rate of 4.41% and post-operative complication rate of 14.70%. Finally, amid 51 patients who underwent trans-abdominal pre-peritoneal approach, post-operative seroma collection was seen in three cases and port site hematoma formation was seen in two cases only.Conclusions: Our results were comparable with various literature demonstrating that laparoscopic surgeries are safe and effective. However, evolution of laparoscopic surgery in developing countries is still slow. Therefore, effective training and availability of required instruments is needed.